Generar un Geo-portal para el grupo de investigación en ciencias ambientales (GRICAM) de la Universidad Politécnica Salesiana. Caso de estudio “Proyecto Pesillo-Imbabura” - Ayala Narea, Gabriel Sebastián (2017)
The present technical work to generate a Geo-portal for the Group of Investigation in Environmental Sciences (GRICAM) of the Salesian Polytechnic University. Case of study "Project Pesillo-Imbabura" intends to form in a web site the information compiled of the project "Threats, vulnerabilities and adjustment in the access to the water. Cases of study: Pesillo - Imbabura ", helping free software and knowledge of information systems, as well as also of applicative that allow to translate information georeferenced, that helps the final users to visualize in a dynamic, organized way and that at the same time is of easy access. At present the access to Internet has turned, another basic fundamental service in the life of the humans, for that reason has improved the way to locate geographic sites, places and peoples, the present project centers in generate a tool that consists of maps with specific layers that present detailed information on the current state of Irrigation Management that present in the most vulnerable sectors of Pesillo-Imbabura. To the being a dynamic web page, also it allows to connect with other projects already developed previously of internal use of the Group GRICAM, such as: “Water management of Human Consumption ", so that access to these applications with their respective information can be manipulated from any place with Internet access, thus providing feedback in less time in these projects.